Batteries: Prescribing Functional Additives for Treating the Poor Performances of High‐Voltage (5 V‐class) LiNi0.5Mn1.5O4/MCMB Li‐Ion Batteries (Adv. Energy Mater. 9/2018). Issue 9 (26th March 2018) - Xu, Gaojie; Pang, Chunguang; Chen, Bingbing; Ma, Jun; Wang, Xiao; Chai, Jingchao; Wang, Qingfu; An, Weizhong; Zhou, Xinhong; Cui, Guanglei; Chen, Liquan
Abstract : In article number1701398 by Guanglei Cui and co‐workers, tris(trimethylsilyl) phosphite (TMSP) and 1, 3‐propanediolcyclic sulfate (PCS) are unprecedentedly prescribed as binary functional additives for treating the poor performances of high‐voltage (5 V‐class) LiNi0.5 Mn1.5 O4 /MCMB (graphitic mesocarbon microbeads) Li‐ion batteries at both room temperature and 50 °C. The high‐voltage LiNi0.5 Mn1.5 O4 /MCMB cell with binary functional additives shows a preponderant discharge capacity retention of 79.5% after 500 cycles at 0.5 C rate at room temperature.